Engineering properties of rocks - Zhang, Lianyang (Elsevier geo-engineering book series ;, 2005)
Having a complete understanding of the properties and behaviours of rock is essential when undertaking any engineering involving them. By drawing on the Authors years of experience in the field this book covers the properties of a number of rocks, and explores discontinuities, strength, deformability and permeability of rock masses and calculations of stress. Author is a consultant following many years experience at MIT Draws together essential data on the properties of various types of rock Offers an inexpensive alternative to in-situ tests.